Targeting STAT3 by HO3867 induces apoptosis in ovarian clear cell carcinoma. Issue 9 (24th July 2017) - Bixel, Kristin; Saini, Uksha; Kumar Bid, Hemant; Fowler, John; Riley, Maria; Wanner, Ross; Deepa Priya Dorayappan, Kalpana; Rajendran, Sneha; Konishi, Ikuo; Matsumura, Noriomi; Cohn, David E.; Selvendiran, Karuppaiyah
Abstract : Advanced ovarian clear cell carcinoma (OCCC) carries a very poor prognosis in large part secondary to the extremely high rate of resistance to standard platinum and taxane chemotherapy. Signal transducer and activator of transcription 3(STAT3) expression and activation has been shown to regulate tumor progression in various human cancers, though has not been well studied in OCCC. Preliminary work in our lab has demonstrated constitutive activation of STAT3 (pSTAT3Tyr705 or pSTAT3727) in OCCC cell lines as well as human OCCC tumor tissue samples. Significantly, pSTAT3 is expressed in the absence of other forms of activated STAT (pSTAT1, 2, 6). Therefore, this work was planned to investigate the role of STAT3 and examine the efficacy of a novel anti‐cancer compound ‐HO‐3867, which is an inhibitor of STAT3, using known OCCC cell lines. Results demonstrate that treatment with HO‐3867 decreased expression of pSTAT3 Tyr705 as well pSTAT3 Ser727, while total STAT3 remained constant. STAT3 overexpression increased the migration capability in OVTOKO cells in vitro and led to an increased tumor size when injected in vivo . The inhibitory effect of HO‐3867 on cell proliferation and cell survival was accompanied by increased apoptosis, within 24 h post treatment. Treatment with HO‐3867 resulted in a decrease in Bcl‐2 and increase of cleavage of caspase 3, caspase 7, and PARP, confirming induction of apoptosis after treatment with HO‐3867. In addition, HO‐3867 significantly inhibited formation of human umbilical vein endothelial cells capillary‐like structures and invasion at both 5 and 10 µM concentrations. STAT3 expression plays an important role in the spread of OCCC in vitro as well as in vivo . Thus, we can exploit the STAT3 pathway for targeted drug therapy. Inhibition of pSTAT3 using HO‐3867in OCCC cell lines appears to be a promising therapy. This is of utmost importance given the poor response of OCCC to standard chemotherapy regimens. Abstract : What's new? The overall clinical response in chemotherapy‐treated patients with recurrent ovarian clear cell carcinoma (OCCC) is only 25–40%. Development of new treatment approaches is urgently needed to improve the survival of patients afflicted with the disease. Here, the authors find high levels of expression of phosphorylated STAT3 (pTyr705 and pSer727) in OCCC and propose that this may represent a new chemoresistant pathway in these cancers.